Impacto del covid 19 en las exportaciones de bienes de la región Loreto, periodo 2019 - 2021 - Mestanza D'Acevedo, Daniela Alexandra (2022)
Covid 19 from 2020 had a negative impact on the economies of the countries and our country could not be the exception, the global confinement measure almost completely paralyzed international trade and the Loreto region also suffered this paralysis, for this reason The main objective of this research is to analyze the impact of covid 19 on the region's exports, both in traditional and non-traditional exports, making a description of the facts as they were developed, the design being non-experimental and cross-sectional, the research showed that traditional exports had a negative variability in the years 2020 and 2021 in 73.1% and 62.3% respectively compared to the year 2019, in the same way non-traditional exports in the years 2020 and 2021 their negative variability was 37.% and 34.8%, also compared to the year 2019, it is finally concluded that the impact on total exports of e region was -69.2% in 2020 and -58.1% in 2021, both compared to 2019, a year in which there was no pandemic.